Peningkatan Hasil Belajar IPA melalui Penerapan Metode Group Investigation - Roslaini Roslaini (Mataram University, 2020)
The purpose of this classroom action research was to find out that the application of the group investigation method in class IX-2 students of SMP Negeri 4 Dumai in the 2019/2020 academic year. This research was conducted in class IX-2 of SMP Negeri 4 Dumai in the even semester of the 2019/2020 learning year. This research was started from January 2020 to February 2020. The subjects of this study were 32 students of class IX-2 of SMP Negeri 4 Dumai, consisting of 18 men and 14 women with heterogeneous abilities. The form of this research is Classroom Action Research (CAR). The results of this study indicate that the application of the group investigation method can improve science learning outcomes in class IX-2 students of SMP Negeri 4 Dumai in the 2019/2020 academic year. The learning outcomes before CAR was 62.8 with a poor category. In the first cycle the student learning outcomes obtained an average of 74.5 in the sufficient category. In the second cycle, there was an increase in student learning outcomes to 81.0 in the good category